Pengaruh Likuiditas, Intensitas Modal, dan Profitabilitas terhadap Kualitas Laba pada Bank BUMN yang terdaftar di Bursa Efek Indonesia Periode Tahun 2022-2024 - Della Angely Br Saragih; Lukita Tripermata; R.M. Rum Hendarmin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
State-owned banks (Bank BUMN) play a vital role in maintaining the stability of the national financial system and are expected to present transparent and high- quality financial reports. One of the key indicators in assessing financial reporting quality is earnings quality, as it reflects the ability of earnings to represent the true economic performance of the company. This study aims to analyze the effect of liquidity, capital intensity, and profitability on earnings quality in state-owned banks listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. This research employs a quantitative approach using secondary data in the form of annual financial reports from five Bank BUMNs over three years. The analytical technique used is multiple linear regression through SPSS software. The study is grounded in signaling theory, which explains how companies convey information to the market through financial disclosures. The findings of this study are expected to contribute to the development of financial accounting literature and serve as an evaluation tool for bank management and stakeholders in improving the accuracy and reliability of financial reporting.